2009
DOI: 10.1177/1059712309342488
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Oriented Modeling of Commons Dilemma Experiments

Abstract: A major challenge in the development of computational models of collective behavior is the empirical validation. Experimental data from a spatially explicit dynamic commons dilemma experiment is used to empirically ground an agent-based model. Three distinct patterns are identified in the data. Two naïve models, random walk and greedy agents, do not produce data that match the patterns. A more comprehensive model is presented that explains how participants make movement and harvest decisions. Using pattern-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Patternoriented modeling (Grimm et al, 2005;Janssen et al, 2009) has been suggested in the socialecological modeling community as an approach to develop more rigorous and comprehensive models. Janssen et al (2009) Pattern-oriented modeling starts from multiple empirically observed patterns, at different scales and hierarchical levels, which are supposed to indicate essential underlying processes and structures of the system.…”
Section: Understanding Transitions: Relevant Experiences In Other Resmentioning
confidence: 99%
“…Patternoriented modeling (Grimm et al, 2005;Janssen et al, 2009) has been suggested in the socialecological modeling community as an approach to develop more rigorous and comprehensive models. Janssen et al (2009) Pattern-oriented modeling starts from multiple empirically observed patterns, at different scales and hierarchical levels, which are supposed to indicate essential underlying processes and structures of the system.…”
Section: Understanding Transitions: Relevant Experiences In Other Resmentioning
confidence: 99%
“…With these laboratory experiments, microsituational variables could be manipulated and rule-crafting could be observed, especially when communications could be recorded because participants were using text-based chat rooms . Using high-resolution experimental data, agent-based models could be tested in a rigorous way (Janssen et al, 2009).…”
Section: Case Study: Dynamics Of Rulesmentioning
confidence: 99%
“…Pattern-Oriented Modeling (POM) is an approach proposed by researchers in ecology to describe the real-world complex systems and design agent-based models accordingly (Janssen et al, 2009). With the ultimate goal to overcome the challenges of covering the complexity and eliciting the uncertainty of the system (Grimm et al, 2005), POM approach is used to explore the internal mechanism of the system (Heckbert et al, 2010).We believe that these methodologies can be applied to tourism and provide a scientific strategy for agent-based simulation in tourism planning.…”
Section: Introductionmentioning
confidence: 99%